0148 Associations Between Subjective and Objective Sleep Outcomes and Nightly Pain Changes in a Chronic Pain Sample. (25th May 2022) - McGovney, Kevin; Curtis, Ashley; McCrae, Christina
Abstract: Introduction: Patients with chronic pain often experience poor sleep. Research demonstrating the bidirectional nature of the pain/sleep association has focused on interindividual patterns based on between person averages, leaving acute, intraindividual patterns based on night-to-night fluctuations understudied. Because both pain and sleep fluctuate considerably, better understanding of those fluctuations may provide important insight into the pain/sleep relationship. Here we examine inter- and intraindividual associations between subjective and objective sleep outcomes and nightly pain changes in individuals with chronic pain and sleep complaints. Methods: Adults with chronic pain and sleep complaints (n=169, Mage=52, SD= 12, 95% female) completed 14 days of actigraphy and sleep diaries each morning and evening. Evening diaries recorded pain and sleep medication use (yes/no), and evening pain intensity (0-none, 100-most intense). Actigraphy and morning diaries recorded sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), and morning pain intensity (0-none, 100-most intense). A nightly pain difference score (morning – evening) was calculated, where positive values indicate worse morning pain relative to previous evening pain. Multi-level models examined the inter- and intraindividual associations between sleep (subjective and objective SOL, WASO, TST) and nightly pain difference scores. Analyses controlled for age, sleep, and pain medication use. Results: Greater interindividual subjective WASO was associated (B=0.06, SE=0.03, p=0.02) with greater interindividual pain difference scores. Other interindividual sleep outcomes (subjective and objective) were not significantly associated with interindividual pain difference scores. There were no associations between sleep outcomes (subjective and objective) and pain difference scores at the intraindividual level. Conclusion: Findings show sleep and pain were not linked at the daily, intraindividual level. However, on average, greater WASO was linked with worse morning relative to evening pain. Thus, although a single night of poor sleep may not impact pain, the buildup of fragmented sleep over time may interfere with restorative properties of sleep and exacerbate morning pain. Future work should investigate mechanisms underlying sleep fragmentation (e.g., sleep architecture, physiological arousal) and how such factors relate to nightly pain changes. Support (If Any): NIH/NIAMS R01AR055160, ClinicalTrials-NCT02001077, PI McCrae.